Poesía y violencia política en los poetas de los años noventa en el Perú (revisión panorámica y estudio del caso de Ya nadie incendia el mundo, de Victoria Guerrero) - Chueca Field, Luis Fernando (2018)
Poets of the “Peruvian poetry of the 1990s” generally avoided to make express reference to the political violence lived in Peru in the 1980s and 1990s. It is a curious fact since that period impacted their lives, during their education and initial participation in the literary field. After 2000, however, many of them decided to face their own silences and wrote books showing not only the will of memory and the critical and lucid view of the process, but also an interesting metapoetic reflection on the possibilities of writing in such situation. All this with an expressive maturity. The purpose of this paper is to present the process of this poetic promotion against the political violence: on the one hand, to investigate the decisive literary, social and ideological factors in the gestation of the mentioned silence and to explore some of the ways in which they processed the violence in their texts. On the other, to point out the circumstances in which they recover the voice and poetic memory about these facts and to mention some of the main concepts developed in these new works. This paper reviews the poetry book Ya nadie incendia el mundo (2005) written by Victoria Guerrero.